Psychometric Evaluation of the ProQOL Version 5 for Assessing Compassion Satisfaction, Burnout and Secondary Traumatic Stress in Nurses (International Journal of Studies in Nursing, 2019)
Background: The Professional Quality of Life scale is commonly used to measure Burnout, Secondary Traumatic Stress, and Compassion Satisfaction in nurses despite a lack of research regarding its psychometric properties in this population. This study evaluates the reliability and validity of the ProQOL version 5 in nurses. Methods: Chronbach’s alpha was used to assess reliability and Confirmatory Factor Analysis was used to test the validity of the three factor structure. Results: Reliability of the Burnout subscale is poor in nurses (α=.53). Confirmatory Factor Analysis revealed the tool’s three factor structure to not be valid in the nursing population (p